2021
DOI: 10.3390/ijerph18041382
|View full text |Cite
|
Sign up to set email alerts
|

Financing Healthcare in Central and Eastern European Countries: How Far Are We from Universal Health Coverage?

Abstract: After the fall of communism, the healthcare systems of Central and Eastern European countries underwent enormous transformation, resulting in departure from publicly financed healthcare. This had significant adverse effects on equity in healthcare, which are still evident. In this paper, we analyzed the role of government and households in financing healthcare in eight countries (EU-8): Czechia, Estonia, Hungary, Latvia, Lithuania, Poland, Slovakia, and Slovenia. A desk research method was applied to collect q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 30 publications
(17 reference statements)
0
24
0
Order By: Relevance
“…However, data show that survival of patients with hematological malignancies has increased dramatically over the last few decades [6][7][8] including patients admitted to the ICU [9]. It is better in Western Europe than in Eastern Europe [10][11][12] which is still suffering from less effective care, fewer resources allocated to heath care [13], limited access to innovative treatment options, higher out-of-pocket spending on health [14,15],…”
Section: Introductionmentioning
confidence: 99%
“…However, data show that survival of patients with hematological malignancies has increased dramatically over the last few decades [6][7][8] including patients admitted to the ICU [9]. It is better in Western Europe than in Eastern Europe [10][11][12] which is still suffering from less effective care, fewer resources allocated to heath care [13], limited access to innovative treatment options, higher out-of-pocket spending on health [14,15],…”
Section: Introductionmentioning
confidence: 99%
“…The evident lag in public spending on health in CEECs entails a shift to the patients' households in the form of out-of-pocket paying. This includes cost sharing (co-payment in a benefit package, direct payments for privately purchased healthcare), and even informal paying that leads to inequality in access to the service [35]. In addition to the complex scenario of lower spending and the higher financial request from households, leading to higher variations in access, CEECs seem to attract increasing interest from corporate and financial investors in medical technology.…”
Section: Structure Disparitiesmentioning
confidence: 99%
“…Additionally, in just the first half of 2018, as many as 13% of Polish adults paid for diagnostic tests out of pocket, mostly because of shorter waiting times in the private sector [58]. Although some studies have reported that the share of out-of-pocket payments in Poland fell considerably [13,54], we still found many people paying for private care despite being entitled to free public services, with the main reason being poor access to public care, particularly in the outpatient sector [56]. Similarly, Polish cancer patients complained about difficulties accessing cancer care, especially about long waiting times for diagnostic tests, doctor's appointments, and treatment.…”
Section: Access To Servicesmentioning
confidence: 99%
“…All of these efforts are of paramount importance because Poland has one of the least resilient health systems in the European Union, as evidenced by higher than average mortality from preventable and treatable causes, lower than average survival rates for cancers, and unsatisfactory screening attendance rates [1]. Other challenges faced by the Polish health system include the low quality of care, long waiting times, health personnel shortages, and a relatively high share of out-of-pocket payments [1,13].…”
Section: Introductionmentioning
confidence: 99%